Determinants Of Breast Self-Exam (BSE) Behavior As Early Detection Of Breast Cancer In Students At Poltekkes Kemenkes Jakarta II - Sri Wiwik Wiyanti; Budiharto Budiharto; Hadi Siswanto (Politeknik Kesehatan Kemenkes Jakarta II, 2022)
Self breast care is one of the early detection methods to find early-stage breast cancer that will be more effective if done as early as possible when women reach reproductive age. Data on Cancer Sub Directorate of the Directorate of Non-Communicable Disease in Indonesia Control at the Ministry of Health there are around 36,761,000 women throughout who have breast cancer.. This study aims to study and explain the determinants of breast self-examination (BSE) behavior as early detection of breast cancer in female students at Poltekkes Kemenkes Jakarta II. The research design used is Cross Sectional. The sample in this study were 295 respondents. Univariate data analysis, bivariate using chi square and multivariate multiple logistic regression with (a <0.05). Variables related to BSE behavior as early detection of breast cancer events were knowledge(p = 0,008), attitudes (p = 0,000), parental support (p = 0,000) role of health personnel (p = 0,000),information media(p=0,000) and age (0,022. Confounding variables are information media (p = 0.191), knowledge (p = 0.136), parental support (p = 0.095). The dominant variable related to breast self-examination (BSE) behavior female student is the role of health workes with Odds Ratio (OR) 6,875.